The Concept of Forgiveness in Hadith and Its Impact on Students’ Social Interaction - Zahra, Naya Nazla Az-; Anwar, Husnel (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Forgiveness is a fundamental moral trait that plays a vital role in shaping harmonious human relationships, fostering peace, and preventing conflict. However, in the context of student life, social interactions are often challenged by misunderstandings and disputes, making forgiveness an essential value to explore. This study aims to examine the concept of forgiveness as reflected in the hadiths of the Prophet Muhammad, its practical application in the social interactions of students at UIN North Sumatra, and the influence of mutual forgiveness on the harmony of the campus social environment. Employing a qualitative descriptive method, data were collected through interviews, documentation, and in-depth analysis. The findings reveal that the practice of forgiveness significantly contributes to the quality of students’ relationships, providing emotional relief, minimizing disputes that may otherwise damage friendships, and fostering a more positive mindset. Moreover, the internalization of forgiveness values strengthens social cohesion and nurtures a peaceful and collaborative academic atmosphere. The study concludes that forgiveness, as derived from prophetic traditions, has been meaningfully integrated into student life at UIN North Sumatra, thereby enhancing interpersonal harmony and supporting the creation of a conducive educational environment. This research contributes to understanding how Islamic ethical values can be practically implemented in modern academic contexts.